Islamic Religious Education Teachers' Strategies in Improving the Al-Qur'an Learning Achievement of Grade XI Students at the Binjai State Islamic Senior High School - Ibnu Jarot Jauhari; Hadi Saputra Panggabean (Cahaya Ilmu Cendekia Publisher, 2025)
Purpose of the study: The study also aims to demonstrate how Qur’anic instructional strategies contribute to shaping students’ discipline, responsibility, cooperation, empathy, and spiritual awareness as essential elements of Character Education. Methodology: This research employs a descriptive qualitative approach. The participants include Islamic Religious Education teachers of Grade XI, with the primary focus placed on the pedagogical strategies they implement. Data were collected through classroom observations, in-depth interviews with teachers, school leaders, and students, and documentation of lesson plans, classroom activities, and assessment records. Data analysis followed Miles and Huberman’s interactive model, involving three stages: data reduction, data display, and conclusion drawing. Main Findings: The findings reveal that teachers implement several transformative learning strategies, including differentiated instruction, peer teaching, digital media integration, and motivational reinforcement. These strategies effectively meet students’ diverse learning needs and significantly improve their Qur’anic recitation performance, tajwid accuracy, and memorization ability. Beyond academic outcomes, these approaches foster crucial social character values such as discipline, collaboration, empathy, perseverance, and responsibility. They also nurture students’ respect for the Qur’an as both a moral compass and a spiritual foundation. Novelty/Originality of this study: This study provides empirical evidence that adaptive and transformative pedagogical strategies within Islamic Religious Education can simultaneously enhance Qur’anic learning outcomes and strengthen socio-moral character formation. Its originality lies in demonstrating how the integration of traditional teaching methods with modern instructional innovations contributes to academic achievement as well as the development of essential moral, social, and spiritual values. The research thus offers a meaningful contribution to contemporary discourse on Character Education in Islamic schooling.